2016
DOI: 10.1017/s003329171600146x
|View full text |Cite
|
Sign up to set email alerts
|

Psychological processes underlying the association between childhood trauma and psychosis in daily life: an experience sampling study

Abstract: BackgroundEvidence has accumulated that implicates childhood trauma in the aetiology of psychosis, but our understanding of the putative psychological processes and mechanisms through which childhood trauma impacts on individuals and contributes to the development of psychosis remains limited. We aimed to investigate whether stress sensitivity and threat anticipation underlie the association between childhood abuse and psychosis.MethodWe used the Experience Sampling Method to measure stress, threat anticipatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
109
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(129 citation statements)
references
References 60 publications
(103 reference statements)
15
109
2
3
Order By: Relevance
“…13 Our findings provide new evidence in support of this proposition, as this is the first ESM study to report that affective disturbance mediates the link from momentary stress to PE in daily life across different stages of early psychosis. In contrast to findings from previous research suggesting some degree of specificity for certain types of stressors for the formation of PE, 18 we found evidence that the effects of all stress variables (ie, event-related, activity-related, and social stress) were mediated via pathways through affective disturbances. Further, while indirect effects of activity-related stress were greatest, there was no strong evidence of differences in magnitude of indirect effects via affective disturbance for different types of stressors.…”
Section: Comparison With Previous Researchcontrasting
confidence: 99%
See 2 more Smart Citations
“…13 Our findings provide new evidence in support of this proposition, as this is the first ESM study to report that affective disturbance mediates the link from momentary stress to PE in daily life across different stages of early psychosis. In contrast to findings from previous research suggesting some degree of specificity for certain types of stressors for the formation of PE, 18 we found evidence that the effects of all stress variables (ie, event-related, activity-related, and social stress) were mediated via pathways through affective disturbances. Further, while indirect effects of activity-related stress were greatest, there was no strong evidence of differences in magnitude of indirect effects via affective disturbance for different types of stressors.…”
Section: Comparison With Previous Researchcontrasting
confidence: 99%
“…These items have been reported to show high levels of internal consistency in previous studies (Cronbach's alpha = 0.80) 37 as well as in the current study (Cronbach's α = 0.90). 18 They have been further shown to have good convergent validity with interviewer-rated measures of psychosis (r = .45, P < .001) the PANSS (r = .45; P < .001) 37 as well as good concurrent validity with negative affect (r = .68, P < .001).…”
Section: Psychotic Experiencesmentioning
confidence: 93%
See 1 more Smart Citation
“…As suggested by Reininghaus et al (2016), early trauma may have an impact on these subjective reactions to later stressors. Indeed, we found that childhood trauma severity correlated with impact, helplessness and perceived danger of later stressful events.…”
Section: Discussionmentioning
confidence: 98%
“…In the context of psychotic disorders, Reininghaus et al (2016) recently found support for the notion that enhanced sensitivity and increased threat anticipation to stress are important psychological mechanisms in the pathways from childhood trauma to psychosis (as put forward by Morgan & Hutchinson, 2010). The question is whether these mechanisms are relevant to the development of psychotic symptoms with a need for care, or merely contribute to a more general vulnerability for psychotic experiences, including those without a need for care.…”
Section: Introductionmentioning
confidence: 99%